Development of Automated Feeding and Security System for Small-Scale Livestock Farm Using Arduino - Adan, Nor Faezah; Abdul Razak, Mohamad Aidil Firdaus; Sufian, Nurul Najiha; Ahamad, Nurizyan Syasya (Penerbit UTHM, 2020)
Livestock agriculture is synonymous to the rural community where they raise and breed livestock to produce milk, meat, eggs, fur, leather and wool for their own consumption. However, due to the global economic changes, livestock agriculture expanded to a profitable business for the farmers not just for local consumption but globally.